The Conservation in Local Wisdom Valuesof ‘Huma Hai’ Djaga Bahen Layout Pattern Case Study: ‘Huma Hai’ Djaga Bahen at Bahu Palawa Village, Central Kalimantan - Fristy Sulistiani; R. Siti Rukayah; Suzanna Ratih Sari (Unika Soegijapranata Semarang, 2018)
Huma Hai (the big house) Djaga Bahen is located on Bahu Palawa village, Kecamatan Kahayan Tengah, Pulang Pisau, Central of Borneo, build in 1933 by Djaga Bahen. This house become the historical witness of the third Serikat Kaharingan Dayak Indonesia (SKDI) III at 1953. In this house is four changes experience at layout pattern the since 1938-1995. Although had experienced such change but there are spaces are still survive and don’t have alteration. It is because of the values of eterily that still hold and maintained by the occupant.In the layout Huma Hai Djaga Bahen than used methods descriftive cualitative. The did occupant about local wisdom values at layout pattern of Huma Hai Djaga Bahen. This based analysis the layout, space organitation, characteristic and space fungtion.The local wisdom values of layout pattern Huma Hai Djaga Bahen is the arrangement or religious advice ancestor of good and bad placement space based on the flow of the river (upstream and downstream) and the sun (east-west). The conservation effort that is by passing arrangement or religious advice ancestor to the next generation hereditary (hereditary Djaga Bahen), without the interference of other parties. By bequeathing it to his descendants, then this historic home can stick either with originality arrangement or religious advice ancestor.